Phonoaudiological rehabilitation of the patient with COVID-19: An integrative review (Research, Society and Development, 2021)
COVID-19 is a disease of the upper respiratory tract, the most severe cases of the disease often require intensive therapy and have acute respiratory distress syndrome (ARDS), requiring prolonged orotracheal intubation and / or reintubation. The development of post-intubation complications is very common and influences the activity of muscles related to swallowing. In this sense, the role of the speech therapist in the multidisciplinary team of patients with COVID-19 is of great importance, especially in rehabilitation after intensive care. Objective: review the available literature on the performance of the speech therapist in patients with COVID-19 undergoing intensive care. Method: This is an integrative literature review carried out in the databases Bireme, Scielo, Science Direct, and PubMed, including studies published in the years 2019 and 2020. Results: It was possible to verify that the performance of the speech therapist it is essential, through the evaluation and speech therapy intervention in order to prevent the condition from getting worse. Studies show that the speech therapist works mainly in swallowing and voice disorders. Conclusion: The speech therapist is an indispensable professional in the treatment of patients with COVID-19, especially patients undergoing orotracheal intubation, because through their therapeutic intervention, it facilitates the work of the other professionals of the multidisciplinary team and enables better quality of life patient.